Diagnosis and treatment of enthesitis-related arthritis - Weiss PF (Dove Medical Press, 2012)
Pamela F WeissDivision of Rheumatology and Center for Pediatric Clinical Effectiveness, The Children's Hospital of Philadelphia, Departments of Pediatrics and Center for Clinical Epidemiology and Biostatistics, University of Pennsylvania School of Medicine, Philadelphia, PA, USAAbstract: Juvenile idiopathic arthritis (JIA) is a chronic, inflammatory disease of unknown etiology. The enthesitis-related arthritis (ERA) JIA category describes a clinically heterogeneous group of children including some who have predominately enthesitis, enthesitis and arthritis, juvenile ankylosing spondylitis, or inflammatory bowel disease-associated arthropathy. ERA accounts for 10%–20% of JIA. Common clinical manifestations of ERA include arthritis, enthesitis, and acute anterior uveitis. Axial disease is also common in children with established ERA. Treatment regimens for ERA, many of them based on adults with rheumatoid arthritis and ankylosing spondylitis, include the use of nonsteroidal anti-inflammatory drugs, disease-modifying antirheumatic drugs, and biologic agents either individually or in combination.Keywords: juvenile arthritis, enthesitis, sacroillitis, epidemiology, therapy